2017
DOI: 10.1037/dev0000290
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual individuation training (but not mere exposure) reduces implicit racial bias in preschool children.

Abstract: Two studies with preschool-age children examined the effectiveness of perceptual individuation training at reducing racial bias (Study 1, N = 32; Study 2, N = 56). We found that training preschool-age children to individuate other-race faces resulted in a reduction in implicit racial bias while mere exposure to other-race faces produced no such effect. We also showed that neither individuation training nor mere exposure reduced explicit racial bias. Theoretically, our findings provide strong evidence for a cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
57
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 72 publications
(143 reference statements)
7
57
1
Order By: Relevance
“…The main finding of a linkage between racial categorization and implicit racial bias points to alternative approaches that can break down this connection. As noted earlier, one approach that has been successful in reducing implicit racial bias with preschool children is training to individuate other‐race faces (Qian et al., ; Xiao et al., ). This method capitalizes on the finding that other‐race recognition is negatively correlated with the tendency to categorize such faces (Ge et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The main finding of a linkage between racial categorization and implicit racial bias points to alternative approaches that can break down this connection. As noted earlier, one approach that has been successful in reducing implicit racial bias with preschool children is training to individuate other‐race faces (Qian et al., ; Xiao et al., ). This method capitalizes on the finding that other‐race recognition is negatively correlated with the tendency to categorize such faces (Ge et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Training significantly reduced implicit racial bias against Africans only for those children who were trained to recognize African faces. Further, Qian et al (2017) found that training Asian children to individuate African faces, but not mere exposure to the African faces, reduced implicit bias against Africans. These findings suggest that young children’s perceptual recognition of other-race faces is causally linked to their implicit racial bias against them, supporting the Perceptual-to-Social Linkage Hypothesis.…”
Section: Social Consequencesmentioning
confidence: 97%
“…This type of bias refers to unconscious stereotypes, prejudices, and discriminatory behaviors based on race. Like the more consciously accessible forms of explicit racial bias, implicit racial bias develops in early childhood between 3 and 6 years of age (Baron & Banaji, ; Dunham, Baron, & Banaji, ; Dunham, Chen, & Banaji, ; Qian et al., , ; Raabe & Beelmann, ; Xiao et al., ), if not earlier (Quinn et al., ; Xiao, Quinn, et al., ; Xiao, Wu, et al., ).…”
mentioning
confidence: 99%
“…For decades there were no reliable ways to measure implicit racial bias in children, and consequently, antiracism educational efforts in childhood have almost exclusively targeted explicit racial bias (Aboud et al., ; Bigler, ; Hitti & Killen, ; Rutland, Hitti, Mulvey, Abrams, & Killen, ). Recent methodological innovations in measuring implicit bias (Baron & Banaji, ; Cvencek, Greenwald, & Meltzoff, , ; Dunham, Baron, & Carey, ; Dunham et al., ; Dunham et al., ; Qian et al., , ; Xiao et al., ) now make it possible to systematically investigate how to reduce it early in life.…”
mentioning
confidence: 99%
See 1 more Smart Citation